GLACIER RETREAT DIFFERENCES IN CHILEAN CENTRAL ANDES AND THEIR RELATION WITH ANTHROPOGENIC BLACK CARBON POLLUTION - F. Cereceda-Balic; F. Cereceda-Balic; M. F. Ruggeri; V. Vidal; V. Vidal (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
Black Carbon (BC) is indicated as the main atmospheric pollutant that obscures snow surfaces and absorbs solar energy, which accelerates the melting of ice/snow and produces glacier retreat. The case of Chile is of particular interest because it has most part of the Andean cryosphere, which has responded strongly to climate change through a retreat of their glaciers, having implications in the availability of freshwater for the inhabitants and economic activities. In this work, the aim was to investigate and quantify for the first time the impact that BC could have on the differences observed in the glacial retreat in the study area, decoupling this impact of the climatic and glaciological factors, through which it has not been possible to explain the difference in glacier behavior in the zone. In this case, two glaciers with comparable characteristics from the Central Andes of Chile were studied: Olivares Alpha Glacier (OAG) and Bello Glacier (BG). The spatio-temporal evolution (2004-2014) was studied using remote sensing images (Landsat). This information was analyzed together with measured data of BC concentrations in air and snow for the year 2014. Results showed important differences in glacier retreat, −27.6% for OAG vs. −5.1% for BG (2004–2014), together with a significantly higher impact of BC in OAG than BG. Regarding the sources of the measured BC, considering that both glaciers are at a similar distance from Santiago, it can be considered that there is another source influencing OAG, which could be the mountain mining activities, considering the small distance existing between this glacier and the mines.